Assessing the impact of green logistics performance on vietnam's export trade to regional comprehensive economic partnership countries - Huong, Vu Thi Thu; Kiem, Pham Van; Thuy, Nguyen Thu; Trang, Vu Thi Huyen; Ha, Hoang Thi Thu (International Journal of Innovative Research and Scientific Studies, 2024)
This article uses a gravity model framework to examine the impact of green logistics on Vietnam's exports to countries participating in the Regional Comprehensive Economic Partnership (RCEP). The study uses a generalized least squares (GLS) estimation method based on panel data for the period 2010-2018 and has reliable sources. The results of empirical research have found the following main findings: (i) Logistics performance, encompassing cost, reliability, and time-related factors, significantly and positively influence Vietnam's exports; (ii) The interaction effects between supply chain input components (customs, infrastructure, and services) and CO2 emissions from the transportation sector have a positive impact on Vietnam's exports; (iii) The supply chain input components demonstrate direct and positive effects on exports when implemented in conjunction with their interaction effects with CO2 emissions from the transportation sector; (iv) The emissions of CO2 from Vietnam's transportation sector exert a negative influence on exports; (v) Adopting a green logistics approach that focuses on reducing CO2 emissions from the transportation sector demonstrates a positive influence on Vietnam's exports. This influence is observed through direct and moderating effects, indicating the potential for sustainable practices to foster export growth. These research findings provide valuable insights for managers and policymakers in the formulation of informed decisions related to the development and promotion of green logistics. By embracing sustainable practices and aligning export growth with environmental goals, Vietnam can enhance its competitiveness while contributing to a greener future.